Study of data center communication network topologies using complex network propagation model - Han, Xu; Huangpeng, Qizi; Gao, Qiannan; Fu, Yude; Duan, Xiaojun (Frontiers in Physics, 2023)
Data center, as the core infrastructure of data storage and processing, calls for network security protection. Numerous detailed measures have been proposed for information security. However, there are few studies that use the characteristics of network topology to suppress the spread of viruses. Different topologies exhibit different characteristics in the face of virus propagation. In this paper, we investigate three types of data center network topologies, i.e. Fat-tree, Leaf-spine, and Bcube, and quantify the propagation characteristics in different topologies through the IC propagation model. The probability of the device being infected p, the count of propagation sources c, the access of propagation sources acc, and the topological parameters are all considered. Given that network security defenders can only change the topology and topological parameters, we propose a computational framework that combines factor analysis, which provides us with the selection of network topological parameters with a low virus propagation rate in the candidate parameter set. Through experiments, we find that Leaf-spine has a good inhibitory effect on viruses with high propagation probability. Meanwhile, the parameter sets obtained from Fat-tree, Leaf-spine, and Bcube have their advantages in different ways. We hope that more data center network topologies will be studied to improve the security of all data centers using these network topologies.